ANÃLISIS Y EVOLUCIÃ“N DE LA ESTRUCTURA DE DEUDA DE LAS EMPRESAS QUE HAN COTIZADO EN LA BOLSA DE MADRID DURANTE EL PERIODO 2006-2011 - Masero, Natividad RodrÃguez; Castellano, Mercedes Mateo; Teba, Alejandro Medrano; Herrera, Silvia RodrÃguez (European Scientific Journal, ESJ, 2013)
The object of this work is the analysis of the evolution and composition of the structure of debt of companies that have been quoted on the Madrid Stock Exchange in the period 2006-2011. The aim of the paper is to know the way of financing of the companies and the influence of the sector to which they belong. On the other hand, we analyse the impact of the crisis in the way of financing for firms. The methodology used has been first and foremost an individual examination of each sector, as well as the evolution and composition of financial structure of each one of them. Through the analysis of the average value has been a comparison between sectors, which shows a difference between them. Finally we have completed a multivariate analysis that confirms our initial hypothesis. The results obtained lead us to conclude that the sector influences decisively in the composition of the financial structure of companies. However, there are exemptions for certain items differentiating between the period prior to the beginning of the crisis and the aftermath.